Child Tuberculosis (TB) Education Through Leaflet – Based Home Visits to Improve Parents' Knowledge in The Service Area of North Sangatta Community Health Center - Poni Angelia; Nurwijayanti (Universitas STRADA Indonesia, 2026)
Tuberculosis (TB) remains a serious public health problem in Indonesia with a high transmission rate. Children have a higher risk of disseminated TB and extrapulmonary disease compared to adults. The purpose of this community service initiative is to determine the effectiveness of childhood tuberculosis education through leaflet media in increasing parents' knowledge in the Working Area of the North Sangatta Health Center. The implementation method used is the Descriptive analysis. The community service activity, in the form of education on the importance of increasing knowledge (education) on tuberculosis prevention in children through leaflet media during home visits to improve parents' knowledge in the working area of the North Sangatta Health Center, was conducted on Monday, March 16, 2026. The counseling activity was conducted in each participant's home. Conclusion: The childhood tuberculosis education activity can increase parents' knowledge at the North Sangatta Health Center. The empowerment of health workers and cadres in improving tuberculosis education for children is expected to be realized effectively through this counseling activity.